Use of Intra-Aortic Balloon Pump (IABP) in Patient with Ventricular Septal Rupture - Purnomo, Yudi; Nuraeni, Aan; Anna, Anastasia; Evangelista, Gabriela (Media Karya Kesehatan, 2023)
Intra-Aortic Balloon Pump (IABP) can be used among patients with Acute Coronary Syndrome (ACS) who experience Ventricular Septal Rupture (VSR) as a form of mechanical support for hemodynamics that has worsened due to cardiogenic shock. As for the cases reported, a 61-year-old male patient with ACS STEMI Infero-Anterior Extensive Killip 4 and VSR experienced chest pain accompanied by shortness of breath. Auscultatory examination found a heart murmur on 3/6 without thrills. The patient had received drugs to improve hemodynamics and was reported to have used an IABP machine. IABP uses semi-auto mode, 1:1 frequency with maximum augmentation. The patient's condition worsened, and he lost consciousness. The patient then had an endotracheal tube connected to a ventilator. Keywords: IABP, Intra-aortic-counterpulsation, ventricular septal rupture.